Difficulty of Management of Retinoblastoma about Two Cases Report in North Benin and Literature Review - ASSAVEDO, ABEL; SOUNOUVOU, Ignace (My University, 2017)
Retinoblastoma is a highly malignant tumor and is the most common intraocular tumor in children. We make two cases report, the first one is about a 3-year-old female of ethnicity Peulh from Beninese origin who has been consulted for an intraocular tumor of the left eye, who is diagnosed retinoblastoma complicated by purulent melt. The symptomatology would have begun around the age of 2 and half years by a leucocoria of left eye associated 3 months later with an exotropia that required multiple treatments by traditional care givers before reference to hospital. The second case concerned a male of 3 years, ethnic of Beninese origin, who consulted for leukocoria of the left eye. The ophthalmological examination in the left eye noticed in the fundus examination a whitish mass superior to 5mm height invading the vitreous cavity. As concerned the right eye, the anterior segment and the fundus examination were normal. The diagnosis evocated is a retinoblastoma in its endophytic form of the left eye. We made literature review about the management of retinoblastoma and difficulties of this management in low income countries.
Keywords: Retinoblastoma; Leukocoria; Strabismus; Intraocular tumor; North Benin